2022
DOI: 10.1097/mpa.0000000000002027
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Pancreatic Intraepithelial Neoplasia in an Autopsy Series

Abstract: ObjectivesPancreatic intraepithelial neoplasia (PanIN) is the currently preferred designation for putative preneoplastic changes in the pancreas. There are few data for the incidence of PanIN in the general population. Our goal was to determine the incidence of PanIN in a large group of pancreases obtained at autopsy.MethodsSlides stained with hematoxylin and eosin were scanned to count PanIN.ResultsWe found multiple PanINs in most pancreases and at least 1 in 86.4% of 154 pancreases when multiple slides (8–12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…Consistent with our KC model, PanIN-1s were always present in the pancreas when PanIN-2 or -3 were identified. These autopsy findings were also confirmed in a separate study (Longnecker and Suriawinata 2022). Thus, our model is concordant with the neoplastic process that occurs in humans and relevant for studying PanIN progression.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with our KC model, PanIN-1s were always present in the pancreas when PanIN-2 or -3 were identified. These autopsy findings were also confirmed in a separate study (Longnecker and Suriawinata 2022). Thus, our model is concordant with the neoplastic process that occurs in humans and relevant for studying PanIN progression.…”
Section: Discussionsupporting
confidence: 84%
“…The majority of the lesions were PanIN-1, with fewer PanIN-2 and PanIN-3 lesions identified (Shi et al 2009); again mirroring the findings in our KC model where there is multifocal lesion formation, and the majority of the lesions at 9 months were PanIN-1 with fewer PanIN-2 and PanIN-3. Moreover, in the study by Shi et al (Shi et al 2009), PanIN lesions were found in the pancreas remote from invasive cancer, which supports the findings from autopsy studies (Matsuda et al 2017; Longnecker and Suriawinata 2022) that not all PanINs progress to cancer. Similar to the etiology of PanINs in our model, greater than 95% of human PanINs harbor a Kras mutation (including 92% of PanIN-1) (Kanda et al 2012), and it is generally accepted that the fraction of Kras -mutant cells in PanINs increases with PanIN grade, indicating clonal expansion of the Kras -mutant cells that have been ‘transformed’ (Kanda et al 2012).…”
Section: Discussionsupporting
confidence: 66%
“…Although previous studies have postulated that multifocal PanIN lesions arise separately, our work definitively demonstrates their independent nature through the development of a technique for integrated 3D modeling and genomic analyses. 6,[37][38][39][40] We found that spatially distinct PanINs most often arise from independent genetic events, exemplified by discordant somatic mutations between spatially discrete lesions. Furthermore, we demonstrate that the proximity of LG or HG PanIN to PDAC does not guarantee shared genetic origins -our cohort included 2 examples of PanINs containing HG dysplasia that were genetically distinct from adjacent PDACs, further emphasizing the importance of 3D genomic analyses to ascertain genetic origins.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, pancreatic intraepithelial neoplasia (PanIN) is microscopic and typically only encountered following resection of other pancreatic pathologies, including overt cancer (11)(12)(13). Autopsy studies -mostly in an older patient population-indicate that PanIN is common in older individuals, however poor preservation of the pancreas due to prolonged warm ischemic time severely limits molecular analysis of autopsy samples (14)(15)(16)(17)(18). The prevalence of PanIN in the general healthy population remains unknown.…”
Section: Introductionmentioning
confidence: 99%